Tendencies and consequences of migration from Ukraine - Nataliia Slaviuk (Наукові записки НаУКМА: Економічні науки, 2022)
The article devotes to the topic of migration from Ukraine. Currently the massive flow of emigrants from Ukraine can be observed, which was caused by the Russian aggression. Definitely, it will influence the Ukrainian economy. In the article the tendencies of emigration from Ukraine since the year 2000 and the current flow and problems are analyzed. The main consequences of emigration in the current conditions are evaluated. It is mentioned that the influence of migration can have a long-lasting effect on the economy of the country. It is obvious that it is important to return people to Ukraine and to take special measures on the governmental and municipal levels. The methodology of econometric analysis is used to analyze the influence of factors on the migration in the country in the pre-war period. It is obvious that the main reason for emigration nowadays is the war in the country, and the decision of people to return will be influenced by the safety in the country, social conditions and the state of economy. It is crucial to define the economic factors, which will influence the decision of people for migration or returning to Ukraine. It is noted that employment and income, economic growth and perspectives of reconstruction and development of the country are important.